Optimizing Branding and E-Commerce Strategies to Strengthen Women's Entrepreneurship in the Melayu Jambi Creative Industry - Muazza Muazza; Mayasari Mayasari; Revis Asra; Iwan Putra; Tohap Pandapotan Simaremare (Yayasan Keluarga Guru Mandiri, 2026)
Women entrepreneurs within the creative sector of the Melayu Jambi community possess substantial potential to boost the local economy through culturally inspired products. Nonetheless, initial field observations and foundational data reveal that 68% of these business owners lack a distinct brand identity, 72% experience restricted access to digital marketing channels, and merely 35% engage actively with e-commerce platforms, leading to diminished market presence and diluted product competitiveness. A gap analysis based on these initial insights and a review of earlier studies shows that most empowerment programs concentrate on general entrepreneurial skills, while integrated branding and e-commerce support rooted in local cultural principles is scarce. Consequently, this initiative seeks to enhance women entrepreneurs' capabilities through culturally infused branding and e-commerce enhancement. The program used a collaborative approach and was implemented in five phases: needs assessment, social outreach, skill development, guidance, and evaluation. The outcomes indicate remarkable advancement in participants' branding acumen and digital proficiency, with average pre-test and post-test scores rising from 47.7% to 77.9%, bolstered by deliverables such as logos, product packaging designs, digital catalogs, and operational e-commerce accounts. In summary, this initiative promotes women's financial autonomy and contributes a culture-centric digital empowerment framework to studies on community-based creative industries.